EXPLORATION OF THE ROLE OF ISLAMIC EDUCATIONAL VALUES IN THE PROCESS OF INDIVIDUAL SOCIAL MOBILITY IN THE BUGIS BONE SOCIETY - A. Nur Nilam Ahdy (Education Studies and Teaching Journal (EDUTECH), 2025)
This study explores the role of Islamic educational values in shaping social mobility within the Bugis Bone community. Using an exploratory qualitative approach through interviews, participant observation, and documentation, the research highlights how values such as honesty, responsibility, hard work, and a strong learning ethic are internalized in family, education, and society. These values serve as cultural capital that drives individuals’ upward mobility, particularly through education and religious roles. Findings show that MI and TPA teachers, young preachers, muezzins, mosque administrators, and other leaders play a strategic role in shaping character and spirituality from childhood to adulthood. Islamic education not only fosters moral and spiritual teachings but also supports vertical mobility through character building, leadership, and involvement in social-economic institutions. The study concludes that strengthening adaptive Islamic education is essential to sustain just, ethical, and Qur’an-based social mobility in the Bugis Bone community.